Solid state battery

By adopting a composite negative electrode sheet structure in lithium-ion batteries, including a current collector substrate, an active metal supplementary layer and a porous carbon fiber layer, the battery life problem caused by dendritic growth is solved, and a solid state with high energy density and long cycle life is achieved Battery simplifies production process.

CN119208535APending Publication Date: 2024-12-27GUANGNA MINGSHANG NEW ENERGY TECH (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411358340.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the circulation process, the growth of dendrites in the existing lithium-ion batteries reacts with the electrolyte, forming dead lithium, resulting in increased internal resistance of the battery, capacity loss and Coulomb efficiency, reducing the cycle life of the battery.

Method used

A solid-state battery is designed, adopting a composite negative electrode sheet structure, including a current collector substrate, an active metal supplementary layer and a porous carbon fiber layer. A solid electrolyte layer is provided on the porous carbon fiber layer, and the solid electrolyte layer is bonded to the positive electrode sheet to achieve Rapid mass transfer and uniform deposition of active metal ions, and supplements the consumed active metal ions during charge and discharge.

Benefits of technology

Through this structure, the Coulomb efficiency and capacity retention rate of the battery are improved, the cycle life of the battery is extended, and the volume expansion of the battery during charging and discharging is avoided, thereby achieving high energy density while simplifying the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208535A_ABST
    Figure CN119208535A_ABST
Patent Text Reader

Abstract

A solid-state battery belongs to the technical field of secondary batteries. The solid-state battery comprises a composite negative pole piece and a positive pole piece, the composite negative pole piece comprises a current collector base material, active metal supplement layers are laminated on the surfaces of the two sides of the current collector base material, porous carbon fiber layers are arranged on the surfaces of the active metal supplement layers, and solid electrolyte layers are arranged on the porous carbon fiber layers; and the solid electrolyte layer is attached to the positive pole piece. The surface of the current collector substrate is provided with a negative electrode structure formed by sequentially overlapping the active metal supplement layer, the porous carbon fiber layer and the solid electrolyte layer, so that the battery has high energy density, the volume expansion of the battery in the charging and discharging process can be avoided, and consumed active metal ions can be supplemented in the charging and discharging process of the battery; the coulombic efficiency and the capacity retention ratio of the battery are effectively improved, so that the battery has long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of secondary batteries, in particular to a solid-state battery. Background Art

[0002] Developing new energy and energy storage technologies is an important strategic measure to meet climate challenges and promote green development. As an important path to achieve the dual carbon goals, new energy vehicles have attracted widespread attention for one of their core technologies, battery technology. Existing lithium-ion batteries use flammable liquid electrolytes, which are difficult to meet the urgent needs of various industries for safety, life, and energy storage. Solid-state batteries with high specific energy, high safety, and long life are considered to be one of the technologies to replace existing lithium-ion batteries and are the next generation of high-performance batteries.

[0003] Metallic lithium is considered to be the first choice for the next generation of negative electrode materials due to its high theoretical specific capacity and low reduction potential. However, when metallic lithium is used directly as the negative electrode, it is easy to cause rapid growth of dendrites during the cycle process; and lithium dendrites will continue to react with the electrolyte to form SEI film, resulting in continuous consumption of metallic lithium and electrolyte and formation of dead lithium, which increases the internal resistance of the battery, causing battery capacity loss and reduced coulombic efficiency, thereby reducing the cycle life of the battery.

[0004] In order to solve the above problems in the prior art, the present invention is provided. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a solid-state battery that can achieve rapid mass transfer and uniform deposition of active metal ions and can replenish active metals in a timely manner.

[0006] The present invention relates to a solid-state battery, comprising: a composite negative electrode sheet and a positive electrode sheet;

[0007] The composite negative electrode plate comprises a current collector substrate, an active metal supplement layer is laminated on both sides of the current collector substrate, a porous carbon fiber layer is disposed on the surface of the active metal supplement layer, and a solid electrolyte layer is disposed on the porous carbon fiber layer;

[0008] The solid electrolyte layer is bonded to the positive electrode plate.

[0009] For some specific embodiments, the active metal supplement layer is an active metal single substance layer or an active metal alloy layer with a thickness of 1 to 200 μm, for example, a thickness of 1 μm, 10 μm, 50 μm, 80 μm, 100 μm, 150 μm, 200 μm, etc.; the active metal is at least one of lithium, sodium, potassium, magnesium, aluminum, zinc, etc., and the active metal alloy layer includes at least one of lithium aluminum alloy, lithium magnesium alloy, lithium boron alloy, sodium potassium alloy, sodium tin alloy, sodium bismuth alloy, aluminum zinc alloy and the like.

[0010] For some specific embodiments, the porosity of the porous carbon fiber layer is greater than 80%, and the specific surface area is greater than 20 g / m 2 , thickness is 10~50μm.

[0011] For some specific implementation schemes, the porous carbon fiber layer includes 70-90 parts of nano-carbon fibers, 1-10 parts of dispersants and 1-20 parts of binders, totaling 100 parts by weight; for example, the weight parts of nano-carbon fibers are 70, 75, 80, 85, 90, etc., the weight parts of dispersants are 1, 4, 6, 10, etc., and the weight parts of binders are 1, 4, 6, 10, 15, 18, 20, etc.; wherein the diameter of the nano-carbon fibers is 50-200nm, the length is 5-20μm, and the aspect ratio is 25-4000.

[0012] For some specific embodiments, the solid electrolyte layer is at least one of an inorganic solid electrolyte layer, a polymer solid electrolyte layer, and an organic-inorganic composite solid electrolyte layer, and has a thickness of 5 to 20 μm, for example, a thickness of 5 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, etc.

[0013] For some specific embodiments, the positive electrode plate includes a positive electrode active material, a conductive agent, a binder, an electrolyte and a current collector, and the positive electrode active material includes at least one of lithium salt, sodium salt, potassium salt, magnesium salt, aluminum salt and zinc salt.

[0014] Compared with the prior art, the present invention has the following technical effects:

[0015] A negative electrode structure in which an active metal supplement layer, a porous carbon fiber layer and a solid electrolyte layer are stacked in sequence is arranged on the surface of the current collector substrate, wherein the solid electrolyte layer is bonded to the positive electrode plate to obtain an effective ion conduction channel; the porous carbon fiber layer is in a three-dimensional network structure, has the characteristics of high porosity and high specific surface area, and can be used to deposit (store) active metal ions migrated from the positive electrode, and can avoid the expansion of the battery volume during charging and discharging while the battery has a high energy density; an active metal supplement layer is arranged between the current collector substrate and the porous carbon fiber layer, so that the active metal ions consumed during the charging and discharging process of the battery can be supplemented, effectively improving the coulombic efficiency and capacity retention rate of the battery, so that the battery has a long cycle life; and the above-mentioned battery structure can be produced using conventional large-scale production processes, and the operation is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of a part of the structure of the solid-state battery in Example 1;

[0017] Figure 2It is a comparison chart of the capacity retention rate of Example 1 and Comparative Example 1;

[0018] 1. Copper foil; 2. Lithium foil; 3. Porous carbon fiber layer; 4. Solid electrolyte layer; 5. Positive electrode membrane; 6. Aluminum foil. DETAILED DESCRIPTION

[0019] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The experimental methods without specific conditions in the examples are carried out according to conventional methods and conditions.

[0020] Example 1

[0021] Preparation of composite negative electrode

[0022] 90 g of carbon nanofiber and 3 g of PVP were added to NMP and ultrasonically mixed for 20 min at an ultrasonic frequency of 100 kHz; then 7 g of PVDF was added and sand-milled at a speed of 2000 rpm for 4 h to obtain a slurry with a mass solid content of 10%;

[0023] The slurry is coated on both sides of the lithium foil-copper foil-lithium foil laminated composite structure, that is, coated on the lithium foil 2 on both sides of the copper foil 1, and then dried in a glove box at 45°C for 4 hours, and the solvent is evaporated to solidify the slurry to obtain a coating, that is, a porous carbon fiber layer 3 with a three-dimensional network structure is formed; the copper foil thickness in the lithium foil-copper foil-lithium foil laminated composite structure is 8μm, and the single-side lithium foil thickness is 4μm; after testing, the thickness of the porous carbon fiber layer is 20μm, and the porosity is 92.1%;

[0024] Dissolve LiClO4 in MMA, stir for 4.5 hours to mix evenly, and prepare an electrolyte with a concentration of 2 mol / L; take 40g of the electrolyte, add ethyl methyl carbonate accounting for 15% (6g) of the electrolyte mass and stir for 5h, then add PVDF accounting for 25% (10g) of the electrolyte mass and stir for 3h to obtain electrolyte slurry; coat the electrolyte slurry on the porous carbon fiber layer, set the heating temperature to 45°C, and keep it warm for 5h to solidify it to form a solid electrolyte layer 4 with a thickness of 20μm; that is, a composite negative electrode sheet is obtained.

[0025] Preparation of positive electrode

[0026] Lithium iron phosphate (LFP): LLZO: CNT: SP: PTFE were mixed in a weight ratio of 84:10:2:1:3, mixed in a ball mill at a rotation speed of 700 rpm for 20 min, and then adjusted to 18000 rpm and mixed for 20 min to obtain a fiberized material;

[0027] The fiberized material was hot pressed on both sides of the aluminum foil 6 with a thickness of 15 μm, and the hot pressing temperature was set to 130°C and the time was 10 s. The obtained positive electrode film 5 had a thickness of 68 μm. The thickness of the final formed positive electrode sheet was 151 μm, and the surface density of the charge was 2.12 mAh / cm 2 .

[0028] Battery Assembly

[0029] The above-mentioned composite negative electrode sheets and positive electrode sheets are alternately stacked in sequence to form a battery cell, such as Figure 1 As shown, the solid-state battery is then packaged with an aluminum-plastic film.

[0030] After testing, the energy density of the solid-state battery is 278Wh / kg; after 300 cycles at 0.5C, the capacity retention rate is 97.63%.

[0031] Example 2

[0032] The difference between this embodiment and embodiment 1 is that:

[0033] In the preparation of the composite negative electrode sheet, the thickness of the porous carbon fiber layer is 24 μm and the porosity is 91.9%;

[0034] In the preparation of the positive electrode sheet, the active material LFP in the positive electrode material was changed to lithium cobalt oxide, and the aluminum foil was 15μm; the thickness of the obtained positive electrode film was 56μm, the thickness of the obtained positive electrode sheet was 127μm, and the surface density of the electricity was 3.07mAh / cm 2 .

[0035] After testing, the final battery has an energy density of 380Wh / kg; after 300 cycles at 0.5C, the capacity retention rate is 97.66%.

[0036] Example 3

[0037] The difference between this embodiment and embodiment 1 is that:

[0038] In the preparation of the composite negative electrode sheet, the lithium foil was replaced by a lithium-magnesium alloy foil with a thickness of 4 μm;

[0039] In the preparation of the positive electrode sheet, the active material LFP in the positive electrode material was changed to lithium nickel cobalt aluminum oxide, and the aluminum foil was 15μm; the thickness of the obtained positive electrode film was 54.5μm, the thickness of the obtained positive electrode sheet was 124μm, and the surface density of the electricity was 3.05mAh / cm 2 .

[0040] After testing, the final battery has an energy density of 377Wh / kg; after 300 cycles at 0.5C, the capacity retention rate is 97.34%.

[0041] Example 4

[0042] Preparation of composite negative electrode

[0043] 84 g of carbon nanofiber and 8 g of PVP were added to NMP and ultrasonically mixed for 20 min at an ultrasonic frequency of 100 kHz; then 8 g of PVDF was added and sand-milled at a speed of 2000 rpm for 4 h to obtain a slurry with a mass solid content of 10%;

[0044] The slurry is coated on both sides of the sodium foil-aluminum foil-sodium foil laminated composite structure, that is, coated on the sodium foil on both sides of the aluminum foil, and dried at 60°C in a glove box for 2 hours to form a porous carbon fiber layer with a three-dimensional network structure; the thickness of the aluminum foil in the sodium foil-aluminum foil-sodium foil laminated composite structure is 8 μm, and the thickness of the single-side sodium foil is 7 μm; after testing, the thickness of the porous carbon fiber layer is 16 μm, and the porosity is 93.8%;

[0045] Sodium tetrafluoroborate (NaBF4) was dissolved in THF, and the mixture was stirred for 6 hours to be evenly mixed to prepare an electrolyte solution with a concentration of 2.5 mol / L; 40 g of the electrolyte solution was added with 10% of fluoroethylene carbonate (FEC) by weight of the electrolyte solution and stirred for 5 hours, and then 23% of PVDF by weight of the electrolyte solution was added and stirred for 3 hours to obtain an electrolyte slurry; the electrolyte slurry was coated on the porous carbon fiber layer, and the heating temperature was set to 60°C, and the mixture was kept warm for 5 hours to solidify the mixture, thereby forming a solid electrolyte layer with a thickness of 20 μm; thus, a composite negative electrode sheet was obtained.

[0046] Preparation of positive electrode

[0047] PVDF was dissolved in NMP to prepare a solution with a concentration of 0.1 mol / L, and sodium iron phosphate, Na3PS4, CNT and SuperP were added thereto, the mass ratio of sodium iron phosphate, Na3PS4, CNT, SuperP and PVDF was 86:8:2:1:3, and the positive electrode slurry was obtained after mixing evenly;

[0048] The positive electrode slurry was coated on both sides of the aluminum foil with a thickness of 10 μm, dried at 100 °C for 12 h, rolled, and then hot pressed. The hot pressing temperature was set at 90 °C and the time was 8 s to obtain the positive electrode sheet. The thickness of the final formed positive electrode film was 56 μm, the thickness of the positive electrode sheet was 122 μm, and the surface density of the charge was 1.6 mAh / cm 2 .

[0049] Battery Assembly

[0050] The composite negative electrode sheets and positive electrode sheets prepared above are alternately stacked in sequence to form a battery cell. The battery cell is packaged with a plastic film to obtain a soft-pack polymer battery, completing the preparation of the solid-state battery.

[0051] After testing, the final battery has an energy density of 173Wh / kg; after 300 cycles at 0.5C, the capacity retention rate is 86.33%.

[0052] Comparative Example 1

[0053] The difference between this comparative example and Example 1 is that:

[0054] In the preparation of the composite negative electrode sheet, only a copper foil with a thickness of 8 μm was provided, and no lithium foil was added; the slurry was coated on both sides of the copper foil with a thickness of 8 μm, and the composite negative electrode sheet was finally made according to the method in Example 1.

[0055] After testing, the final battery has an energy density of 282Wh / kg.

[0056] like Figure 2 As shown, by comparing the battery cycle performance of Example 1 and Comparative Example 1, Example 1 not only always has a higher capacity retention rate than Comparative Example 1, but also after 300 cycles at 0.5C, the capacity retention rate of Example 1 is close to 98%, while Comparative Example 1 does not exceed 90%, but is only 85.04%.

[0057] Comparative Example 2

[0058] The difference between this comparative example and Example 2 is that:

[0059] In the preparation of the composite negative electrode plate, only a copper foil with a thickness of 8 μm was provided, and no lithium foil was added; the slurry was coated on both sides of the copper foil with a thickness of 8 μm, and the composite negative electrode plate was finally made according to the method in Example 2; after testing, the thickness of the porous carbon fiber layer was 22 μm and the porosity was 92.5%.

[0060] After testing, the final battery has an energy density of 378Wh / kg; after 300 cycles at 0.5C, the capacity retention rate is 86.59%.

[0061] Comparative Example 3

[0062] The difference between this comparative example and Example 3 is that:

[0063] In the preparation of the composite negative electrode sheet, only a copper foil with a thickness of 8 μm was provided, and no lithium foil was added; the slurry was coated on both sides of the copper foil with a thickness of 8 μm, and the composite negative electrode sheet was finally made according to the method in Example 3; after testing, the thickness of the porous carbon fiber layer was 20 μm and the porosity was 92.4%.

[0064] After testing, the final battery has an energy density of 371Wh / kg; after 300 cycles at 0.5C, the capacity retention rate is 86.33%.

[0065] Comparative Example 4

[0066] The difference between this comparative example and Example 4 is that:

[0067] In the preparation of the composite negative electrode sheet, only an aluminum foil with a thickness of 8 μm was provided, and no sodium foil was added; the slurry was coated on both sides of the aluminum foil with a thickness of 8 μm, and the composite negative electrode sheet was finally made according to the method in Example 4; after testing, the thickness of the porous carbon fiber layer was 17 μm and the porosity was 93.8%.

[0068] After testing, the final battery has an energy density of 184Wh / kg; after 100 cycles at 0.5C, the capacity retention rate is 83.51%.

[0069] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A solid-state battery, characterized in that: include: Composite negative electrode sheet and positive electrode sheet; The composite negative electrode plate comprises a current collector substrate, an active metal supplement layer is laminated on both sides of the current collector substrate, a porous carbon fiber layer is disposed on the surface of the active metal supplement layer, and a solid electrolyte layer is disposed on the porous carbon fiber layer; The solid electrolyte layer is bonded to the positive electrode plate.

2. The solid-state battery according to claim 1, characterized in that: The active metal supplement layer is an active metal single substance layer or an active metal alloy layer with a thickness of 1 to 200 μm; the active metal is at least one of lithium, sodium, potassium, magnesium, aluminum, and zinc, and the active metal alloy layer includes at least one of lithium aluminum alloy, lithium magnesium alloy, lithium boron alloy, sodium potassium alloy, sodium tin alloy, sodium bismuth alloy, and aluminum zinc alloy.

3. The solid-state battery according to claim 1, characterized in that: The porosity of the porous carbon fiber layer is greater than 80%, and the specific surface area is greater than 20 g / m 2 , thickness is 10~50μm.

4. The solid-state battery according to claim 3, characterized in that: In terms of weight, the porous carbon fiber layer includes 70 to 90 parts of nano-carbon fibers, 1 to 10 parts of dispersants and 1 to 20 parts of binders, totaling 100 parts; wherein the diameter of the nano-carbon fibers is 50 to 200 nm, the length is 5 to 20 μm, and the aspect ratio is 25 to 4000.

5. The solid-state battery according to claim 1, characterized in that: The solid electrolyte layer is at least one of an inorganic solid electrolyte layer, a polymer solid electrolyte layer, and an organic-inorganic composite solid electrolyte layer, and has a thickness of 5 to 20 μm.

6. The solid-state battery according to claim 1, characterized in that: The positive electrode plate includes a positive electrode active material, a conductive agent, a binder, an electrolyte and a current collector, and the positive electrode active material includes at least one of lithium salt, sodium salt, potassium salt, magnesium salt, aluminum salt and zinc salt.